2024
DOI: 10.3390/su16062325
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Potential of Agrivoltaic Systems in Apple Cultivation—A Hungarian Case Study

Aidana Chalgynbayeva,
Péter Balogh,
László Szőllősi
et al.

Abstract: Agrivoltaic systems (AVS) allow the simultaneous use of land—as a limited resource—for crop production and electricity generation. This paper introduces the development prospects of AVS in Hungary with insights into international trends. The most important part is a complex economic analysis and a unit cost analysis of a 38 MWp capacity AVS, considering the most typical basic data in electricity and apple production. The applied risk analysis is based on a Monte Carlo simulation, the distribution function, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…By 2014, China country already reached 1.18 GW of electricity production, which is still increasing due to novel emerging technologies. Cultivation on the agrivoltaic farms includes crops like tea, grapes, kiwifruit, vegetables, and mushrooms [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2014, China country already reached 1.18 GW of electricity production, which is still increasing due to novel emerging technologies. Cultivation on the agrivoltaic farms includes crops like tea, grapes, kiwifruit, vegetables, and mushrooms [17].…”
Section: Introductionmentioning
confidence: 99%
“…In India, agrivoltaic farms are mainly devoted to experimental purposes with different crops, as is the case in Germany, which has vegetable crops, such as winter wheat, potato, and cabbage, but no fruit crops beneath the panels [17].…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate these issues, efforts are being made to introduce agrivoltaic systems. Agrivoltaic systems aim to establish systems where solar panels and cultivation can coexist, with the core concept being the utilization of the space beneath solar panels for agricultural purposes [12][13][14]. Studies, such as that by Jamil et al, have reported that applying agrivoltaic methods to just 1% of Canada's farmland could satisfy at least a quarter of the nation's electricity demand [15].…”
Section: Introductionmentioning
confidence: 99%